Civil Responsibility for Sexual Abuses by Public Services (Analysis of Sexual Harassment Casses by the Chief of KPU R.I) - Salwani, Dinda; Erwin Syahbana, Tengku (Dinasti Research, 2024)
The General Election Commission is a state institution that organizes General Elections in Indonesia. It consists of commissioners who have competence in their field of work. The selection of commissioners as public officials is based on the results of the selection committee selection which is then recommended to the President, for further suitability testing at Commission II of the Republic of Indonesia DPR. Commissioners who pass the suitability test will then be appointed by the President for a term of five years. As public officials, KPU commissioners are those who are believed to have very good personalities and have never been involved in any legal violations. They work based on applicable laws and the KPU code of ethics. The KPU commissioners will elect one of them to be appointed as Chairman of the KPU. The General Election Commission itself is headquartered in Jakarta. This research is normative juridical descriptive, a research method that seeks to describe and interpret the object of research according to what it is, aiming to provide data resulting from researching a situation or existing facts which will then be described clearly so that it can be accepted and understood as to the basis for imposition. the legal rules that apply to the Chairman of the KPU who commits a violation of the law, the legal consequences of the sexual harassment he commits and the form of accountability of the Chairman of the KPU for violations of the law both ethically and regarding the application of criminal law. The results of the research in this paper found that the Chairman of the KPU, based on the facts of the code of ethics trial held by the DKPP, was legally and clearly proven to have violated the KPU code of ethics as Chairman of the KPU for his actions of sexually harassing a female subordinate who served on the Overseas Election Committee in The Hague. , Dutch. Confirming all acts of sexual harassment as stated in the DKPP decision Number 90/PKE-DKPP/V/2024, dated 3 July 2024. With responsibility, he was permanently dismissed as Chairman of the Indonesian KPU.